(3GdCQHYhf MOjKkGs - (3eMeO Hf CHj HcQs
(3ChdgG (B:s
(3HYO GdHSedI ; hGdMeOdI hGdJUdjI CeG HYO aEf GdYHO GdePfH eMeO Hf CHj HcQ hLO aj MOjK NjQ GdEfSGf (B( (3cPG (B) (3UGMH GdeYLRGJ hGdHQgGf Cfg ef LeY CQHYjf MOjKG agh aj GdYah hGdZaQGf aLeY GdYHO CQHYjf MOjKG HGdESfGO GdeJUd Edi GdfHj Udi Gddg Ydjg hSde hRGO GdYHO eG jdjb ddehGYX ef GdMcGjGJ GdeSehYGJs
(3BNQgG (B:s
(3bGdhG cja jYjThf aj Pdc GdReGf bGd cGdOhO aj GdNd bGdhG (B( ) (3Gddg cja jMaXhf Ojfge bGd (B: (3cGdLeQ aj GdjO Ef JQc WaF hEf CNP GMJQbs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc hhba (B: (3eMeO Mfja GdgfOjs
Keywords: (3GdMOjK hGdeUWdMs